Abdominal Wall Reconstruction: The Uncertainty of the Impact of Drain Duration upon Outcomes. Issue 3 (March 2016) - Plymale, Margaret A.; Harris, Jennifer W.; Davenport, Daniel L.; Smith, Nicholas; Levy, Salomon; Roth, J. Scott
Drains are commonly used after abdominal wall reconstruction (AWR) to prevent seroma formation. Drain management is subjective, and the merits and drawbacks of drains are not well understood. After receiving Institutional Review Board approval, we queried our prospectively maintained surgical database for AWR cases from 2009 to 2012 to ascertain if the number of days postoperatively that drains are left in place impacts the incidence of surgical site complications. Number of drains, drain duration, wound complications, and interval to development of complications were recorded. Wound complications were defined as superficial cellulitis, seroma, hematoma, superficial infection, and deep infection. Among 117 AWRs, we investigated the 64 cases with Centers for Disease Control grade one wound classification. Longest drain duration varied widely (2–171 days postoperatively; mean = 22 days). Cases were divided into four groups based on duration prior to removal of all drains: ≤ 7 days (n = 18), 8 to 14 days (n = 16), 15 to 28 days (n = 18), or ≥29 days (n = 12). No significant relationship was found between incidence of seroma/hematoma and days postoperatively of last drain removal. Wound complications increased linearly with drain time. Using logistic regression to adjust for obesity (body mass index >35kg/m 2 ), drain duration >2 weeks and operative time >220 minutes, only body mass index >35 remained an independent predictor of wound occurrence, P < 0.05. Wound complications occur frequently after AWR. Wound infections occur more commonly among patients with drains in place for more than 2 weeks. Strategies to reduce drain duration require furthermore investigation.